Developing personalized recovery strategies for athletes: methods and approaches - Ivan, F. (American Journal of Sports Science, 2023)
(Background) In the world of professional sports today, a major challenge is the demanding schedule that athletes face. To perform at their best in professional leagues, athletes must be in top shape every week for the demanding and lengthy games. This necessitates the use of tools and resources by strength and conditioning coaches to optimize individual recovery strategies for athletes. The article discusses the importance of recovery in sports performance and the benefits of implementing personalized recovery strategies for athletes. It provides methods and approaches for developing personalized recovery strategies, including athlete assessment and specific recovery techniques such as sleep, nutrition, hydration, stretching, massage, compression garments, and active recovery. (Purpose)The goal is to optimize an athlete's recovery and overall athletic performance by tailoring recovery strategies to their individual needs. (Methods) The present study employs a variety of research methods, including a review of existing literature, on-field investigations, and mathematical analysis, to investigate the current state of recovery tools and techniques that can assist in developing effective individualized recovery strategies. (Conclusion) This article emphasizes the importance of assessing an athlete's specific recovery needs, selecting appropriate recovery techniques, and monitoring outcomes to develop personalized recovery strategies. Coaches, trainers, and athletes should adopt a combination of approaches, such as the time-based and individualized approaches, to create effective recovery strategies that can be adjusted as needed to ensure peak performance and overall well-being.